1993
DOI: 10.1007/bf00012862
|View full text |Cite
|
Sign up to set email alerts
|

Soil boron and selenium removal by three plant species

Abstract: High concentrations of boron (B) and selenium (Se) naturally found in the environment are detrimental to sustainable agriculture in the western USA. Greenhouse pot experiments were conducted to study B and Se uptake in three different plant species; Brassica juncea (L.) Czern (wild brown mustard), Festuca arundinacea Schreb. L. (tall fescue), and Brassica napus (canola) were grown in soil containing naturally occurring concentrations of 3.00 mg extractable B kg-1 and 1.17 mg total Se kg-1 soil. During the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…Aydın and Çakır, 2009;Bañuelos et al, 1993aBañuelos et al, , 1993bDel-Campo Marín and Oron, 2007;Santos et al, 2010;Tassi et al, 2011). Bañuelos et al (1993a) found that Indian mustard (Brassica juncea), tall fescue (Festuca arundinacea), bird's-foot trefoil (Lotus corniculatus), and kenaf (Hibiscus cannibinus) reduced extractable soil boron by 52% in field experiments.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Aydın and Çakır, 2009;Bañuelos et al, 1993aBañuelos et al, , 1993bDel-Campo Marín and Oron, 2007;Santos et al, 2010;Tassi et al, 2011). Bañuelos et al (1993a) found that Indian mustard (Brassica juncea), tall fescue (Festuca arundinacea), bird's-foot trefoil (Lotus corniculatus), and kenaf (Hibiscus cannibinus) reduced extractable soil boron by 52% in field experiments.…”
Section: Introductionmentioning
confidence: 97%
“…The most common treatment practice is leaching (Leyshon and Jame, 1993), but this presents several limitations: (1) large volumes of water are required (Bingham et al, 1972), restricting its application in arid and semiarid regions; (2) removal is often incomplete, i.e., only the soluble fraction is removed, which leaves the sorbed fraction that can recharge the soil solution later (Peryea et al, 1985); and (3) soils must have good drainage capacity (Nable et al, 1997). In addition, the collection of the boron-enriched leachate is necessary to prevent contamination of adjacent sites (Bañuelos et al, 1993b). Another treatment method is to replace the surface soil with soil that has low boron levels; however, this treatment is expensive and the boron from subsurface layers can migrate and recharge the overlying non-contaminated soil (Nable et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Greenhouse pot experiments were conducted to study B uptake by different plant species, Brassica juncea (L.) Czern (wild brown mustard), Festuca arundinacea Schreb. L. (tall fescue), and Brassica napus (canola) (Banuelos et al, 1993). Results showed that the greatest total amount of above ground biomass and below surface biomass was produced by tall fescue and the highest concentrations of tissue B were from roots of tall fescue.…”
Section: Boronmentioning
confidence: 83%
“…Generally, Se content in plants increases with the level of Se available and decreases with the sulphur supply. Se concentrations in plant tissues were found to be similar in three different plant species: Brassica juncea (L.) Czern (wild brown mustard), Festuca arundinacea Schreb L. (tall fescue) and Brassica napus (canola) when these were grown in soil containing naturally occurring concentrations of 1.77 mg total Se kg-' in greenhouse pot experiments (Banuelos et al, 1993).…”
Section: Seleniummentioning
confidence: 99%
“…Selenium phytoremediation as phytoextraction (17) and "phytovolatilization" (18) have both been explored. More recently, transgenic plants have been shown to reduce Hg from the more hazardous ionic and methylated forms to Hg(0), which is then volatilized (19).…”
Section: Phytoremediation Of Inorganic Contaminationmentioning
confidence: 99%